2011
DOI: 10.1073/pnas.1109551108
|View full text |Cite
|
Sign up to set email alerts
|

Extensive changes to alternative splicing patterns following allopolyploidy in natural and resynthesized polyploids

Abstract: Polyploidy has been a common process during the evolution of eukaryotes, especially plants, leading to speciation and the evolution of new gene functions. Gene expression levels and patterns can change, and gene silencing can occur in allopolyploids-phenomena sometimes referred to as "transcriptome shock." Alternative splicing (AS) creates multiple mature mRNAs from a single type of precursor mRNA. Here we examined the evolution of AS patterns after polyploidy, with natural and two resynthesized allotetraploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 41 publications
(57 reference statements)
1
89
0
Order By: Relevance
“…Other studies exclusively identified divergent evolution in noncoding regions, while the coding sequence or gene function remained highly conserved. This was true for a duplicated gene pair of the argonaute (Ago) family, encoding AGO proteins important for small RNA mediated gene silencing (McFarlane et al, 2011), and for IGFBP-2 genes, binding and regulating actions of Insulinlike growth factor (Zhou et al, 2011). None of these studies reported identical expression patterns of TS-WGD duplicates, emphasizing that changes in regulatory elements are very common after WGD.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Other studies exclusively identified divergent evolution in noncoding regions, while the coding sequence or gene function remained highly conserved. This was true for a duplicated gene pair of the argonaute (Ago) family, encoding AGO proteins important for small RNA mediated gene silencing (McFarlane et al, 2011), and for IGFBP-2 genes, binding and regulating actions of Insulinlike growth factor (Zhou et al, 2011). None of these studies reported identical expression patterns of TS-WGD duplicates, emphasizing that changes in regulatory elements are very common after WGD.…”
mentioning
confidence: 87%
“…Divergence of splicing events can principally play a role after polyploidization as shown in a study in plants (Brassicaceae) (Zhou et al, 2011). In this study natural and resynthesized tetraploid species were compared to a closely related diploid species in terms of splicing patterns of paralogous genes.…”
mentioning
confidence: 99%
“…It has been demonstrated that, in some cases, allopolyploids can survive in a broader range of environments than their progenitors. This can be due to greater gene regulatory flexibility as a result of homologspecific gene regulation (Dong and Adams, 2011;Combes et al, 2012) or alternative splicing (Zhou et al, 2011) in response to environmental perturbation. However, there remains a need for more empirical evidence demonstrating ecological differentiation facilitated by allopolyploidy (Abbott et al, 2013;Madlung, 2013;Soltis et al, 2014).…”
Section: Hybrid Speciationmentioning
confidence: 99%
“…The negative correlation between AS and duplication may relate to the 'expense' of operating the AS machinery: if the cost of generating multiple isoforms through AS is high, then selection would favour reducing it in those cases where multiple isoforms may be present through other mechanisms, such as gene duplication or polyploidy. Initial investigations of AS in relation to gene and genome duplication in plants have focused on Arabidopsis [70], Brassica napus [71] and wheat [72]. Additional studies of the role of AS in generating novel isoforms in polyploids are needed; for further information on AS in polyploids, see Yoo et al [23].…”
Section: (C) Novelty In Gene Expressionmentioning
confidence: 99%